2001
DOI: 10.1542/peds.107.4.683
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Preterm Infants Fed Nutrient-Enriched or Term Formula After Hospital Discharge

Abstract: Growth was improved in preterm infants fed a nutrient-enriched postdischarge formula after hospital discharge to 12 months' CA. Beneficial effects were most evident among infants with birth weights <1250 g, particularly for head circumference measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
69
1
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(83 citation statements)
references
References 38 publications
9
69
1
4
Order By: Relevance
“…Our results are similar to other studies 8,13,14 that evaluated the effects of a high-nutrient formula after discharge. Friel et al 13 reported on 52 infants <1500 g birth weight who were randomly assigned to either a nutrient-enriched formula or a standard term formula when the infants achieved a weight of 1850 g. Infants were then maintained on the assigned formula for 6 months and followed for 12 months.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results are similar to other studies 8,13,14 that evaluated the effects of a high-nutrient formula after discharge. Friel et al 13 reported on 52 infants <1500 g birth weight who were randomly assigned to either a nutrient-enriched formula or a standard term formula when the infants achieved a weight of 1850 g. Infants were then maintained on the assigned formula for 6 months and followed for 12 months.…”
Section: Discussionsupporting
confidence: 91%
“…Studies comparing unfortified and fortified human milk with fortified formulas have shown decreased bone mineralization and linear growth among infants receiving human milk. 10,21,25,26 In summary, our findings support prior reports 8,13,14 of improved growth for VLBW infants receiving TF. One difference between our observational study and the three trials was duration of TF.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…15 Three recent studies add additional insight into the role for PDF, suggesting benefits may be related to birth weight, 16 gender, [16][17][18] and/or a 'window of opportunity' when supplemental nutrients can promote 'catch-up' and subsequent growth even after discontinuation of PDF. 13,14 Two of the reports also raise the possibility that postdischarge nutrition may benefit long-term development.…”
Section: Introductionmentioning
confidence: 99%